Planering av vindkraft i Sápmi - Näsman, Rut (2016)
Urfolk runt om i världen har blivit utsatta för koloniala maktstrukturer sedan ett par århundraden tillbaka. Genom juridiska handlingar och fysiska intrång på urfolks marker har stater tagit makten över land och resurser. Målet med uppsatsen är att förstå om och i så fall hur dessa strukturer spelar in i dagens planering av vindkraftsutbyggnaden i norra Sverige där urfolket samer lever. Frågeställningar som berör kolonial historia, samiskt kulturarv och hur detta påverkas av vindkraftsutbyggnaden ställs mot hållbarhet i form av social rättvisa som teoretisk grund. En litteraturstudie av skrivet material om vindkraft och rennäring resulterar i en slutsats som svarar till frågan huruvida de koloniala maktstrukturerna går att återspegla i dagens planering. Planeringen av vindkraft i norra Sverige inkräktar på samers markrättigheter och därmed rennäringen och det samiska kulturarvet. Indigenous communities around the world have been exposed to colonial oppression for hundreds of years. Governments often use their legal frameworks to intrude on indigenous lifestyles in order to gain control of lands and resources they portray as crucial to economic expansion. Today's drive for renewable energy resources has prompted Sweden's government to develop wind farms on indigenous lands in the north of Sweden. The arguments for doing so mirror the expansion of hydroelectric capacity of the 20th century, namely that the expansion of renewable resources constitute a common good and the government should proceed in the name of public interest. The underlying issues concern sustainability and colonialism. A literature study of current Swedish spatial planning practices highlights the ongoing neglect of Sami interests. Planning practices in the north of Sweden present a direct threat to indigenous cultural heritage and the livelihood of traditional practices such as reindeer herding.